Assessing impacts of climate changes extremes and land use/land cover changes on surface water quality in Letaba Catchment, South Africa - Mohlala, Grace (My University, 2024)
Water, a fundamental resource, plays a crucial role in human prosperity, and its relationship with climate dynamics and land use patterns is critical, particularly in semi-arid regions. This study assesses the impact of climate change and land-use/land-cover (LULC) changes on surface water quality within the Letaba Catchment. Remote sensing and GIS techniques provided valuable insights into land use changes, showcasing the effectiveness of the Random Forest classifier algorithm. The analysis of precipitation patterns over three key years (1986, 1994, and 2018) reveals substantial variations, uncovering the localised nature of rainfall influenced by geographical factors. The transition from 1986 to 1994 revealed noteworthy shifts, including an increase in forestry (6% to 13%) and built-up areas (11% to 12%), while water bodies experienced a significant reduction from 13% to 5%. The subsequent leap to 2018 continued this transformation, with further decreases in water bodies, forestry, and vegetation, and notable expansions in built-up areas, cultivated land, and barren land. This analysis showed the impacts of both natural processes and anthropogenic developments on the Letaba catchment's landscape. Examining surface water quality parameters, the study revealed a concerning decline in pH levels in 2018, indicating acidity and suggesting potential implications for aquatic life. Despite this, phosphorus, and Chemical Oxygen Demand (COD) levels adhered to acceptable standards, emphasizing the ecosystem's resilience to maintain nutrient balance. The analysis of the complex interaction between rainfall, LULC changes, and surface water quality parameters revelled intriguing insights. For the years 1986, 1994, and 2018, no significant connection was observed between electrical conductivity and rainfall. The examination of non-linear connections, crucial in understanding the impacts of LULC changes on the dynamics of surface water quality, highlighted the nuanced relationships captured through Spearman rank correlation. This study provides important analysis into the evolving surface water quality parameters of the Letaba Catchment, emphasising the impact of temporal dynamics, climate, and anthropogenic impacts on landscape and surface water quality.
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2024
Keywords: Climate extremes and land use changes; Surface water quality parameters; GEE; Random Forest classifier; Rainfall patterns; Pearson correlation coefficients; Spearman rank correlation; Climatic changes -- South Africa -- Limpopo; Water quality -- South Africa -- Limpopo; Water quality -- Measurement; Watersheds